APAKAH ANAK LAKI-LAKI HARUS LEBIH UNGGUL SEBUAH TELAAH KONSEP JENDER - Meutiawati, Tia (Jurnal Penelitian Humaniora, 2015)
Abstract This research aimed at understanding the role of parents in educating their children and whether parent's treatment still reflects gender discrimination. Population of this research was students of SLTP IV Yogyakarta in 2000/2001. The number of sample was 120 students selected randomly. Data was collected by means questioner distribution. The results showed that parent's treatment toward their children is equal (there were no significant difference) within 20 kinds of learning process interaction. Nevertheless, there is a kind of treatment that reflects a gender discrimination; that is, a boy is more promoted to reach higher school report book mark that his classmates. The implication of this research is a difference of sexual concept and gender concept necessarily to be implanted as a fundamental of treating their children in education. Keywords: gender discrimination, sexual concept, gender concept